فاعلية أفق التوقع والمسافة الجمالية في قراءة النّص الشّعري -قصيدة قارئة الفنجان لنزار قباني أنموذجاً- - مصطفى, روشن عبدالستار; علي, آريان رسول (Sulaimani Journal for Humanities, 2022)
Reading is an important communicative process in receiving texts، especially poetic texts. As it is the most important way to receive the ideas and culture of the author or writer through the text and a sense of the desired meaning. A poem was chosen from among the poems of the modern poet Nizar Qabbani as an applied model, due to its suitability in that it opens to the recipient the doors of interpretation and multiple readings. In this research, the role of the reception theory was determined through the efforts of Hans Robert yaws who is one of the most famous pioneers of this theory in giving the main role of the reader through the reading process as he is the receiver of these texts and the interpreter of the meanings contained in those texts. Also، this theory was applied to the poem Qari’at al- Fanjan by the Syrian poet Nizar Qabbani according to the concept of yaws in the horizon of expectation and aesthetic distance. The nature of the research necessitated dividing it into one introduction and two sections, so the first topic came on the propositions of Yaws، and the second topic came about a reading in the poem Qari’at al-Fanjan according to the concepts of the horizon of expectation and the aesthetic distance of Yaws.The research relied on the analytical method، in addition to the descriptive method.